2015
DOI: 10.3762/bjnano.6.124
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and in vitro effects of 7 nm alloyed silver–gold nanoparticles

Abstract: SummaryAlloyed silver–gold nanoparticles were prepared in nine different metal compositions with silver/gold molar ratios of ranging from 90:10 to 10:90. The one-pot synthesis in aqueous medium can easily be modified to gain control over the final particle diameter and the stabilizing agents. The purification of the particles to remove synthesis by-products (which is an important factor for subsequent in vitro experiments) was carried out by multiple ultracentrifugation steps. Characterization by transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…For an extended X-ray diffraction and TEM-EDX analysis of the alloy nanoparticles we refer to Ristig et al, 15,36 who demonstrated that the used synthesis method produces AgAu alloy nanoparticles of adjustable composition, with an increased Au content in the center of the particle. In agreement to their nding, the UV-vis absorption spectrum (Cary 60 UV-vis spectrophotometer by Agilent Technologies Inc.) of the nanoparticle suspension used herein showed a plasmon resonance absorption peak at 447 nm (see Fig.…”
Section: Np Characterizationmentioning
confidence: 99%
“…For an extended X-ray diffraction and TEM-EDX analysis of the alloy nanoparticles we refer to Ristig et al, 15,36 who demonstrated that the used synthesis method produces AgAu alloy nanoparticles of adjustable composition, with an increased Au content in the center of the particle. In agreement to their nding, the UV-vis absorption spectrum (Cary 60 UV-vis spectrophotometer by Agilent Technologies Inc.) of the nanoparticle suspension used herein showed a plasmon resonance absorption peak at 447 nm (see Fig.…”
Section: Np Characterizationmentioning
confidence: 99%
“…19 This in turn will determine their chemical and biological effects, e.g. the release of silver ions for antibacterial activity 20 and the presence of gold on the nanoparticle surface for a stable subsequent covalent functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption peak of the as-synthesized Ag/Au NCs shifts to the ultraviolet region ( figure 1(a)). This manifests two phenomena, the first one is due to the higher molar ratio of Ag with respect to Au precursor [15,31]. As for pure Ag NCs absorption peak is in the UV region (ca.…”
Section: Resultsmentioning
confidence: 96%